Una larga adolescencia hacia una democracia moderna. Análisis psicosocial de elecciones congresales especiales 2020 - Montero López, Víctor Eusebio (2020)
The results of the 2020 special congressional elections are analyzed in terms of participation, voting option, as well as preferential voting; the psychosocial reasons for which these results were obtained and what the political parties and their presidential and congressional projections 2021 are at the moment are explained. It is concluded that there is strong questioning of the political class, indicating many aspects that we lack in leadership, ability to govern and modern vision to transform the country.